“You Pretend to Pay Me; I Pretend to Work”: A Multi‐Level Exploration of Quiet Quitting in the Greek Context - Georgiadou, Andri; Vezyridis, Paraskevas; Glaveli, Niki (Human Resource Management, 2025)
ABSTRACT This study explores quiet quitting—a distinct form of workplace withdrawal—in the Greek context, adopting a multilevel approach to understand how cultural, institutional and individual factors shape this emerging phenomenon. Drawing upon relevant literature, we investigate the macro, meso‐organizational, and micro‐individual level factors that shape the emergence and persistence of quiet quitting. Through a qualitative, interview‐based methodology, we engage with a diverse sample of Greek Human Resource (HR) managers to capture their perceptions and lived experiences of the factors that contribute to quiet quitting. Our findings highlight the complex interplay between societal shifts, cultural norms, organizational practices, and individual coping mechanisms that give rise to and sustain quiet quitting behaviors. We propose a conceptual framework that situates quiet quitting within the unique socio‐cultural, economic, and institutional realities of the Greek context. This framework reveals how quiet quitting manifests as a dynamic process, initiated by psychological contract breaches and perpetuated through cycles of emotional exhaustion and identity rationalization. By providing a holistic understanding of the quiet quitting phenomenon, this study contributes to the advancement of contextualized Human Resource Management (HRM) research and offers valuable insights for practitioners navigating the challenges of the modern workplace.